Case Analysis of Bowl Rotation Performance Deficiency in the FO Purifier of MV Manalagi Tara - Robertus Constantin Farrel; Amad Narto; Utari, Riyadini (LPPM AKMI SUAKA BAHARI CIREBON, 2025)
Abstract The FO purifier auxiliary aircraft on board is a critical auxiliary machine in the fuel system. It separates fuel oil from air, mud, and dirt. When the researcher was conducting sea practice on the MV Manalagi Tara, the FO purifier auxiliary aircraft experienced damage, resulting in the release of oil into the sludge channel of the FO purifier, which caused a decrease in FO purifier performance. Then, the FO purifier was immediately turned off by Engineer Four before more oil came out, which caused a reduction in fuel oil. Purpose - This study is to determine the factors causing the reduced performance of the bowl rotation on the FO purifier, the impact of the malfunction of the bowl rotation, and the failed performance of the bowl rotation on the FO purifier. Methodology – The research method employed in this thesis is qualitative, utilizing the fishbone analysis technique. Findings – The results from this study indicate that the factors causing the lack of bowl rotation performance on the FO purifier are dirty bowls, loose flat belts, damaged bowl shaft bearings, and worn bowl shafts. The impacts are caused by factors contributing to the lack of bowl rotation performance on the purifier. Efforts that can be made so that the rotation performance on the FO purifier can operate normally are cleaning the FO purifier bowl, adjusting the flat belt, replacing the bearing shaft, and the shaft bowl with new ones. Originality – Understanding of mechanical condition and material degradation influence purifier performance in real ship operation